The role of new social communication technologies in changing public sphere and PR - Demeterffy Lančić, Renata (Видавництво Львівської політехніки, 2013)
The author discusses the importance of new communication technologies from two aspects: at the development of pluralistic public sphere as a local and global sphere and public relations as a special type of communication action. The author highlights the important effects of new communication technologies on public relations, and its ability to manipulate and reshape global public sphere, as well as, possibility of new public sphere to change PR.
Keywords: PR; public sphere; social communication technologies; new media; internet; manipulation; education